Afflexivity in post-qualitative inquiry: prioritising affect and reflexivity in the evaluation of a health information website. Issue 3 (2nd September 2021) - Setchell, Jenny; Olson, Rebecca; Turpin, Merrill; Costa, Nathalia; Barlott, Tim; O'Halloran, Kate; Wigginton, Britta; Hodges, Paul
ABSTRACT: Increasingly, people turn to online sources for health information, creating human-non-human relationalities. Health websites are considered accessible in scope and convenience but can have limited capacity to accommodate complexities. There are concerns about who gets to 'assemble' with these resources, and who is excluded. Guided by Ahmed's socio-political theories of emotions, we questioned our feelings as we intra-acted with a consumer information website about back pain (MyBackPain). This encouraged us to approach resource evaluation in a way that alters conventional rational/cognitive judgement processes. Our inquiry was 'supra-disciplinary' involving public health, sociology, allied health and consumer collaborators. Specifically, we considered relationality – the feelings circulating between bodies/objects and implicated in MyBackPain's affective practices; impressions – the marks, images or beliefs MyBackPain makes on bodies/objects; and directionality – how these intra-actions pushed in some directions and away from others. Although Ahmed would likely not consider herself 'post-humanist', we argue that her socio-political theories of how objects and emotions entangle are of great interest to furthering critical post-human understandings of health. Rather than threatening decision-making, we suggest that feelings (and their affects) are central to it. The article demonstrates the productive potential of critical post-human inquiry in identifying/countering 'othering' possibilities, and catalysing a 'nomadic shift' towards new human-non-human formations.